EFFICACY OF THE CLINICAL-INSTRUMENTAL ALGORITHM IN THE TREATMENT OF SPINAL TANDEM STENOSIS - Vadim Anatol'evich Byvaltsev; Andrei Andreevich Kalinin; Valerii Vladimirovich Shepelev; Yurii Yakovlevich Pestryakov (Coluna/Columna, 2019)
ABSTRACT Objective: To conduct a multicenter analysis of the effectiveness of surgical tactics for treating patients with symptomatic tandem stenosis of the cervical and lumbar spine, based on a differentiated clinical-instrumental algorithm. Methods: The study included 97 patients with symptomatic tandem stenosis of the cervical and lumbar spine. The patients were allocated into 2 groups. The main prospective follow-up group (Group I) consisted of patients (n=46) who had undergone staged decompression/stabilization surgery according to the surgical tactics developed based on the differential clinical-instrumental algorithm. The clinical comparison group (Group II) (n=51) consisted of retrospectively recruited patients who, depending on the prevailing clinical condition, underwent primary surgery at the cervical level (29 cases) or at the lumbar level (22 cases). Results: The comparative analysis in Group I revealed significantly better parameters in the clinical and instrumental data. The total rates of postoperative surgical complications in the cervical and lumbar spine were 15% in Group I and 68% in Group II (p=0.0014). Conclusion: The multicenter analysis of the clinical-instrumental algorithm based on differential application of decompression/stabilization techniques enabled more rational and radical surgery, with less adverse outcomes, leading to earlier start of rehabilitation in the prospective group of patients (Group I), and an objective improvement in long-term clinical and functional outcomes. Level of Evidence II; Prognostic Studies - Investigating the Effect of a Patient Characteristic on Disease Outcome.